Model Hybrid COBIT 2019 dan PLS-SEM untuk Mengukur Determinan Efektifitas Informasi Tata Kelola TI - Bansoma, Meinahen; Hanna M. Baun (The Indonesian Journal of Computer Science, 2025)
In terms of improving the quality and service of the University through the role of tech-nology, it is important to measure the maturity of IT Governance management. However, there are still many organizations with IT governance management that are not aligned with the goals of the University. Therefore, this study will measure the influence of in-formation determinants on innovation and performance to assess the maturity of IT man-agement. This research was conducted at Citra Bangsa University (UCB) Kupang, East Nusa Tenggara. The PLS-SEM model is used to measure the effect of innovation and per-formance, while the IT maturity analysis will use the 2019 COBIT model. In this study, to get responses from respondents, questionnaires were distribut-ed containing hypotheses about the influence of information determi-nants on innovation and performance. As a re-sult, 98 questionnaires with complete criteria were collected, these responses were then ana-lyzed using PLS-SEM. After analyzing the influence of information determinants, then proceed to assess the maturity of IT management in the present. The results show that APO04 and BAI11 get an average gap score at level 1 with values from the DSS01, BAI04, APO11, APO12, APO02 processes at levels 0 and 1. This shows that IT manage-ment still needs improvement in order to create harmony between management IT with the University's Goals, Vision, Mission and strate-gy.